Effectiveness of a Transdiagnostic Educational Package Based on Cognitive Behavioral Therapy, Schema Therapy, and Meaning Therapy on Psychological Well-being and Marital Burnout in Women Experiencing Emotional Divorce - Nazemi Zand, Nikta; Ghorban Shiroudi, Shohreh; Khalatbari, Javad; Rahmani, Mohammadali (Psychology of Woman Journal, 2023)
Objective: The present study aimed to determine the effectiveness of transdiagnostic treatment based on cognitive behavioral therapy, schema therapy, and meaning therapy on psychological well-being and marital burnout in women experiencing emotional divorce.Methods and Materials: The method of this study was quasi-experimental, with a pre-test and post-test design with a control group. The study population included all female clients who attended counseling centers in Tehran, diagnosed with conditions of emotional divorce in their marital life in the year 2021. The study sample consisted of 30 women experiencing emotional divorce, who were selected through stratified random sampling and placed into the educational group based on transdiagnostic treatment involving cognitive behavioral therapy, schema therapy, and meaning therapy (15 participants) and the control group (15 participants). The measurement tools used in the research included: the Psychological Well-being Scale by Ryff (1989), Marital Burnout Scale by Pines (1996), Marital Conflict Scale by Barati and Sanaei (1999), and Emotional Divorce Scale by Gottman (2008). Data were analyzed using covariance analysis and SPSS software version 20.Findings: The results indicated that the treatment based on transdiagnostic cognitive therapy, schema therapy, and meaning therapy has an effect on reducing marital burnout (F=109.71, P